2001
DOI: 10.1029/2000gl011652
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil moisture anomalies on variability of the North American Monsoon System

Abstract: Abstract. We examine the influence of land-atmosphere interactions, as moderated by soil moisture anomalies, on variability of the North American Monsoon System (NAMS). Sensitivity experiments, in which soil moisture was prescribed to field capacity, were completed with the MM5 mesoscale model linked to the OSU land surface scheme. Our results demonstrate that the NAMS precipitation response to soil moisture forcing depends critically on the location of anomalous surface conditions. Wet soil in the southern Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
97
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 11 publications
(15 reference statements)
11
97
1
Order By: Relevance
“…The sensitivity found in this study is greater than that found in a similar study by Small (2001), which investigated the effect of artificial soilmoisture anomalies on tropospheric ridge structure and regional precipitation patterns during the NAM. Small (2001) reported changes in regional precipitation patterns on the order of 20%. In the present study, differences in precipitation are several hundreds of percent in some basins.…”
Section: Discussioncontrasting
confidence: 82%
“…The sensitivity found in this study is greater than that found in a similar study by Small (2001), which investigated the effect of artificial soilmoisture anomalies on tropospheric ridge structure and regional precipitation patterns during the NAM. Small (2001) reported changes in regional precipitation patterns on the order of 20%. In the present study, differences in precipitation are several hundreds of percent in some basins.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, a positive feedback mechanism is found in a large region extending from northwestern Mexico to the southwestern United States (Small, 2001;. Bosilovich et al (2003) conclude in their study with water vapour tracers that the wettest monsoons have mostly continental sources, while drier monsoons have less local sources of precipitation.…”
Section: Introductionmentioning
confidence: 93%
“…As a result, prior studies have explored whether the NAM region in the southwestern U.S. and northwest Mexico exhibits a feedback mechanism between the land surface states and the atmospheric conditions leading to precipitation generation. For instance, a positive soil moisture-precipitation feedback has been identified using regional climate models (e.g., Small, 2001;Xu et al, 2004;Vivoni et al, 2009). Using a global model, Feng et al (2013) found that a positive soil moisture-precipitation feedback was limited to the northern (more arid) sections of the NAM region, while a negative feedback was apparent in more southerly (tropical) areas.…”
Section: Introductionmentioning
confidence: 99%